Selection of EPS-producing Lactobacillus strains isolated from kefir grains and rheological characterization of the fermented milks - Hamet, Maria Fernanda (2015)
In this study the ability to produce exopolysaccharides during growth in milk of 28 Lactobacillus, previously isolated from kefir grain, was investigated and the rheological properties of the obtained fermented milks were also studied. During fermentation all microorganisms were able to produce polysaccharide with final concentration ranging from 20 mg L-1 to 370 mg L-1. Lactobacillus kefiranofaciens and Lactobacillus plantarum strains produced oligosaccharide with low degree of polymerization. The exopolysaccharides produced by the five Lactobacillus paracasei strains presented also a high molecular weight fraction. In consequence the acid milk gels obtained by fermentation with all the L. paracasei strains were the ones that presented the highest viscosities. Nevertheless the viscolestic characteristics of the resulting acid gels were different. L. paracasei CIDCA 83123 produces a milk having a viscous behavior whereas fermented milks with L. paracasei CIDCA 8339, CIDCA 83120, CIDCA 83121 and CIDCA 83124 has gel structure. The five L. paracasei strains isolated from kefir studied in the present work were the first described that produce high molecular weight exopolysaccharides. Since production of high molecular weight exopolysaccharides affects the viscosity of fermented milk these strains could have a successful application improving texture of fermented dairy product.